INVESTIGATING THE RELATIONSHIP BETWEEN LONELINESS AND SOCIAL ISOLATION WITH INFLAMMATION: A SYSTEMATIC REVIEW. (11th November 2018) - Smith, K; Stewart, S; Riddell PhD, N; Victor, C
Abstract: Loneliness and social isolation have been linked with an increased risk of the development of chronic illness, however, the mechanisms driving this association remain unclear. One possible reason could be that they are linked with increased inflammation. Seven databases were searched by two reviewers for synonyms of "loneliness" and "inflammation". Inclusion criteria included a population of adults aged 16 or older, examining the association of loneliness or social isolation with an outcome of inflammation. Eleven studies were identified that examined loneliness and inflammation, of which six indicated a significant relationship. Thirteen studies were identified that examined social isolation and inflammatation, of which twelve noted a significant association. There was notable heterogeneity between studies for population studied, confounder control, study design, measures of loneliness or social isolation and inflammatory outcome. Implications of these results in terms of understanding the link between loneliness and social isolation with chronic illness will be discussed.